1995
DOI: 10.1073/pnas.92.18.8378
|View full text |Cite
|
Sign up to set email alerts
|

Identification of C1q as the heat-labile serum cofactor required for immune complexes to stimulate endothelial expression of the adhesion molecules E-selectin and intercellular and vascular cell adhesion molecules 1.

Abstract: To examine the role of complement components as regulators of the expression of endothelial adhesive molecules in response to immune complexes (ICs), we determined whether ICs stimulate both endothelial adhesiveness for leukocytes and expression of E-selectin and intercellular and vascular cell adhesion molecules 1 (ICAM-1 and VCAM-1). We found that ICs [bovine serum albumin (BSA)-anti-BSA] stimulated endothelial cell adhesiveness for added leukocytes in the presence of complement-sufficient normal human serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 37 publications
4
64
0
2
Order By: Relevance
“…This was not surprising since these receptors are found predominantly inside the cell and are expressed on resting ECs in a low number that increases upon cell exposure to pro-inflammatory stimuli, such as LPS, TNF␣ and IFN␥ (Guo et al, 1999) although this remains a controversial issue (Oroszlan et al, 2007). In addition, C1q has been shown to bind to C1qRs with high affinity only when immobilized on polystyrene plate, heat-treated or bound to ICs, suggesting that the conformational changes of the molecule may favour its interaction with the ligand (Lozada et al, 1995;Steino et al, 2004;van den Berg et al, 1998). Heparan sulphates present on the surface of ECs offer an alternative to C1qRs in binding C1q, as suggested by our data showing that treatment of DECs with heparinase removes a substantial portion of bound C1q.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was not surprising since these receptors are found predominantly inside the cell and are expressed on resting ECs in a low number that increases upon cell exposure to pro-inflammatory stimuli, such as LPS, TNF␣ and IFN␥ (Guo et al, 1999) although this remains a controversial issue (Oroszlan et al, 2007). In addition, C1q has been shown to bind to C1qRs with high affinity only when immobilized on polystyrene plate, heat-treated or bound to ICs, suggesting that the conformational changes of the molecule may favour its interaction with the ligand (Lozada et al, 1995;Steino et al, 2004;van den Berg et al, 1998). Heparan sulphates present on the surface of ECs offer an alternative to C1qRs in binding C1q, as suggested by our data showing that treatment of DECs with heparinase removes a substantial portion of bound C1q.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of C1q to C1qRs has been shown to induce diverse biologic effects including cell adhesion and spreading, expression of the adhesion molecules E-selectin, ICAM-1 and VCAM-1 (Lozada et al, 1995) and production of IL-6, IL-8 and monocyte chemoattractant protein-1 (van den Berg et al, 1998). However, cC1qR and gC1qR are unlikely to be involved in the binding of C1q because we failed to identify bands corresponding to either of the two C1qRs in western blot analysis of C1q purified from DECs by affinity chromatography and to obtain positive signals when the same preparation was examined by a sandwich capture ELISA using antibodies to C1q and to each C1qR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that CRP can directly bind to C1q, 25 which we confirm by SPR, where C1q bound CRP captured by anti-CRP antibody (supplemental Figure 6A-B). However, CRP binding to C1q is unlikely to explain the mechanism of CRP enhancement of phagocyte responses toward IgG1-opsonized platelets, as the effect was observed with purified CRP in the absence of serum ( Figure 3B-E) and after serum heat inactivation, for which C1q is sensitive 26 ( Figure 2A). In further support of this, we did not find C1q binding to spotted IgG1 to facilitate additional CRP binding (supplemental Figure 6B-C), nor did captured C1q by spotted antiC1q antibodies provide a platform for CRP binding (supplemental Figure 6B-C).…”
Section: Fc-dependent Platelet Activation Exposes Crp Ligands Recognmentioning
confidence: 98%
“…Among these molecules, receptors for the collagen-like (cC1q-R or collectin receptor, a homolog of calreticulin (CR) 3 ) (1-3), and globular domains (gC1q-R/p33 (also known as p32)) (4,5), of the complement component C1q, have been identified and implicated in various ligand-mediated functions. In addition, endothelial cells have been shown to express C1qRp, a highly glycosylated, membrane-spanning molecule implicated in the enhancement of Fc-and C3b-mediated phagocytosis (6,7). Although both cC1q-R/CR and gC1q-R/p33 lack a transmembrane segment and have been thought to be found predominantly inside the cell, it is now believed that both molecules have a multicompartmental localization, including on the cell surface (8 -11).…”
mentioning
confidence: 99%